Selective Redundancy Removal: A Framework for Data Hiding - Ugo Fiore (Future Internet, 2010)
Data hiding techniques have so far concentrated on adding or modifying irrelevant information in order to hide a message. However, files in widespread use, such as HTML documents, usually exhibit high redundancy levels, caused by code-generation programs. Such redundancy may be removed by means of optimization software. Redundancy removal, if applied selectively, enables information hiding. This work introduces Selective Redundancy Removal (SRR) as a framework for hiding data. An example application of the framework is given in terms of hiding information in HTML documents. Non-uniformity across documents may raise alarms. Nevertheless, selective application of optimization techniques might be due to the legitimate use of optimization software not supporting all the optimization methods, or configured to not use all of them.